Spike protein evolution in the SARS-CoV-2 Delta variant of concern: a case series from Northern Lombardy. Issue 1 (1st January 2021) - Baj, Andreina; Novazzi, Federica; Drago Ferrante, Francesca; Genoni, Angelo; Tettamanzi, Elena; Catanoso, Giuseppe; Dalla Gasperina, Daniela; Dentali, Francesco; Focosi, Daniele; Maggi, Fabrizio
ABSTRACT: The SARS-CoV-2 variant of concern (VOC) "Delta" is currently defined by PANGOLIN as a cluster of 33 different AY sublineages. Delta (in particular B.1.617.2) is largely and rapidly replacing the Alpha VOC as the dominant clade in most countries. To date, variations in the Spike protein of the Delta VOC have largely been limited. We report here the results of a genomic surveillance programme from Northern Italy. We identified several Delta sublineages harbouring mutations previously reported in GISAID at extremely low frequencies and in different combinations. Two patients (one of them vaccinated) tested positive for a Delta sublineage harbouring S71F, T250I, T572I and K854N. More patients tested positive for G769 V plus C1248F, A352S, and R158G and C1248F, respectively. Genomic surveillance of Delta variants should be encouraged to anticipate immune escape and deploy countermeasures.